Histone Methylation of H3K4 Involved in the Anorexia of Carnivorous Mandarin Fish (Siniperca chuatsi) After Feeding on a Carbohydrate-Rich Diet - You, Jun-Jie; Ren, Ping; He, Shan; Liang, Xu-Fang; Xiao, Qian-Qian; Zhang, Yan-Peng (Frontiers in Endocrinology, 2020)
Food intake of carnivorous fish decreases after feeding on a carbohydrate-rich diet. However, the molecular mechanism underlying the anorexia caused by high-carbohydrate diets has remained elusive. We domesticated the mandarin fish to feed on carbohydrate-rich diets (8%), after 61 days of feeding, several fish fed on artificial diet well during the whole feeding period, named Group A; the other fish fed on artificial diet well at the beginning, but the food intake decreased to 1/2 (anorexia), even did not eat artificial diets for 5 days, named Group B; and we set a negative control named Group C, which fed with live prey fish through the experimental process.. The plasma glucose was significantly higher in the mandarin fish of Group B than that of Group A, whereas hepatic glycogen and plasma triglyceride were significantly lower. Using transcriptome sequencing, we investigated the differentially expressed genes between Group A and B, and excluded the genes that did not differentially expressed between Group A and C. The activation of mTOR and Jak/STAT pathways were found in the mandarin fish with anorexia, which was consistent with the higher expression levels of pepck and pomc genes. We found the higher expression of histone methyltransferase setd1b gene and the increased H3K4me3 (histone H3 tri-methylated at lysine 4) in the fish of Group B. Furthermore, using ChIP assay and inhibitor treatment, we found that the up-regulated H3K4me3 could activate the pepck expression, which might be contributed to the hyperglycemia and anorexia in the mandarin fish fed on carbohydrate-rich diets. Our study initially indicated a link between histone methylation and pepck expression, which might be a novel regulatory mechanism of food intake in fish with a carbohydrate-rich diet.